Strategi Pengelolaan Limbah Padat Domestik Berbasis Pemberdayaan Masyarakat Di Kota Dumai - Sri Ramadhani; Ridwan Manda Putra; Syahril Nedi (Pelantar Press, 2023)
The problem of domestic solid waste has become a national issue, including in Dumai City, as seen in the Landfill (TPA) in Dumai City (Mekar Sari Landfill, South Dumai District). Many and easy domestic solid waste are found in the landfill, which is caused by not being able to be handled considering that 3 sanitary landfills are full and limited human resources, land and tools. This study aims to determine the implementation and constraints, environmental, social and economic impacts of domestic solid waste management in West Dumai District and South Dumai District. The research was conducted in several stages, starting from an initial survey based on field observations and interviews using variables of waste types and sources in West Dumai District and South Dumai District, the volume of waste, the impact on the environment, social and economic, the form of management implementation, and the constraints possessed in the management. This study used non-probability sampling with snowball sampling method in sampling techniques. This method is used in connection with the collection of interview-based information/data, and multilevel questionnaires, ranging from waste producers, management officers to supervisors of domestic waste management in West Dumai District and South Dumai District of Dumai City. Based on the results of the study, domestic solid waste in West Dumai and South Dumai Districts of Dumai City will continue to increase along with the higher volume of waste produced compared to what can be handled by managers (less than 60%) while the obstacles they have cannot be resolved. Suboptimal management of domestic solid waste has a negative impact on the environment in West Dumai and South Dumai Districts. Among them are triggering easy flooding when it rains, to contamination of water sources used by humans. From a social aspect, the comfort of Dumai residents is disturbed, including their daily activities. From an economic point of view, flooding has an impact on income levels (economic aspects). Flooding (tidal) is increasingly routine in West Dumai and South Dumai Districts with an increasingly tight frequency, namely 2 times / month, which is caused by the topography of the area (lower than other areas) and clogged waterways due to garbage carried by the water flow. The suggestion in this study is to propose management collaboration with companies operating in Dumai in supporting the operation of the 3R TPS, such as financing for operators, providing machines, or for facility maintenance.